2018
DOI: 10.1038/s41537-018-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

Impairment in delay discounting in schizophrenia and schizoaffective disorder but not primary mood disorders

Abstract: A measure of planning and impulse control, the delay-discounting (DD) task estimates the extent to which an individual decreases the perceived value of a reward as the reward is delayed. We examined cross-disorder performance between healthy controls (n = 88), individuals with bipolar disorder (n = 23), major depressive disorder (n = 43), and primary psychotic disorders (schizophrenia and schizoaffective disorder; n = 51) on the DD task (using a $10 delayed larger reward), as well as the interaction of DD scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 30 publications
2
27
0
Order By: Relevance
“…As mentioned previously, a proactive coping style is often associated with impairments in attention and cognitive flexibility, as well as heightened impulsivity (for a review see Coppens et al, 2010). These traits have in turn been associated with schizophrenia in patients (Brown et al, 2018; Ho et al, 2018). Thus, using both psychometric impulsivity scales and the delay discounting task (a measure of action planning and impulse control in which higher rates of reward discounting, due to the preference of smaller and immediate rewards over delayed and larger ones, reflect enhanced impulsivity), it has been shown that impulsivity measures are positively associated in a consistent manner with schizophrenia, schizoaffective disorder, and schizophrenia risk in unaffected biological relatives of patients (Ahn et al, 2011; Brown et al, 2018; Ho et al, 2018).…”
Section: Rha Rats As a Model Of Deficits In Attentional Processes Comentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, a proactive coping style is often associated with impairments in attention and cognitive flexibility, as well as heightened impulsivity (for a review see Coppens et al, 2010). These traits have in turn been associated with schizophrenia in patients (Brown et al, 2018; Ho et al, 2018). Thus, using both psychometric impulsivity scales and the delay discounting task (a measure of action planning and impulse control in which higher rates of reward discounting, due to the preference of smaller and immediate rewards over delayed and larger ones, reflect enhanced impulsivity), it has been shown that impulsivity measures are positively associated in a consistent manner with schizophrenia, schizoaffective disorder, and schizophrenia risk in unaffected biological relatives of patients (Ahn et al, 2011; Brown et al, 2018; Ho et al, 2018).…”
Section: Rha Rats As a Model Of Deficits In Attentional Processes Comentioning
confidence: 99%
“…These traits have in turn been associated with schizophrenia in patients (Brown et al, 2018; Ho et al, 2018). Thus, using both psychometric impulsivity scales and the delay discounting task (a measure of action planning and impulse control in which higher rates of reward discounting, due to the preference of smaller and immediate rewards over delayed and larger ones, reflect enhanced impulsivity), it has been shown that impulsivity measures are positively associated in a consistent manner with schizophrenia, schizoaffective disorder, and schizophrenia risk in unaffected biological relatives of patients (Ahn et al, 2011; Brown et al, 2018; Ho et al, 2018). In addition, the presence of heightened impulsivity in schizophrenia is paralleled by impairments in working memory (Ahn et al, 2011; Brown et al, 2018).…”
Section: Rha Rats As a Model Of Deficits In Attentional Processes Comentioning
confidence: 99%
“…However, this correlation was found when we considered hyperbolic parameter k (supplementary information), an aspect that deserves future investigation. These results are only partly in line with evidence that schizophrenia patients prefer more immediate rather than delayed rewards compared to healthy controls 1013 . We should however mention that the results of the majority of the study on patients were based on the hyperbolic model and used monetary rewards.…”
Section: Discussionmentioning
confidence: 64%
“…Abnormal temporal and effort discounting of rewards characterizes several forms of psychopathology, including schizophrenia 3,9 . By and large, individuals with schizophrenia seem to choose immediate over long-term rewards more frequently than healthy controls, whether in monetary choice questionnaires 10,11 or intertemporal choice tasks 12,13 . However, although impaired working memory has frequently been found associated with higher discounting rates 10,11 , cognitive dysfunction alone does not seem to fully account for the abnormal discounting of rewards observed in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, neither diagnosis nor anhedonia was associated with discounting rate. Prior behavioral studies have reported elevated discount rates in SCZ (49,(67)(68)(69)(70), although results are mixed in mood disorders (68,(70)(71)(72)(73)(74)(75). Although not statistically significant in our sample, we observed a trend in individuals with SCZ to discount more than others.…”
Section: Discussionmentioning
confidence: 99%